New 1H-pyrazolo[3,4-d]pyrimidin-1-yl)ethyl)-2-phenylisoquinoline-1(2H)-ones as Phosphoinositide 3-kinase Inhibitors for Treating Cancer and Other Diseases - De, Surya K. (Recent Patents on Anti-Cancer Drug Discovery, 2024)
The patent describes novel useful compounds, such as PI3K protein kinase inhibitors, in particular as PI3K delta (δ) and/or gamma (γ) protein kinase modulators. The present disclosure also provides methods for preparing PI3K protein kinase inhibitors, pharmaceutical compositions containing them, and methods of treatment, prevention, and amelioration of PI3K kinase-mediated diseases, and disorders.
Keywords: cancer